FROM “CLERGY” TO “CELIBACY:”: THE DEVELOPMENT OF RAHBĀNĪYYAH BETWEEN THE QUR’ĀN, ḤADĪTH AND CHURCH CANON - El-Badawi, Emran (Al-Bayān, 2013)
The term rahbānīyyah is used differently in the Qur’ān than it is in the ḥadīth and subsequent classical Islamic literature. The former discusses the term in the context of clergy and religious leadership, and the latter in the context of celibacy and marriage. This shift in meaning may be taken into account by examining Christian legal texts that were contemporaneous with the Qur’ān on the one hand, and the hadīth on the other. These texts are the Didascalia Apostolorum and the canons of the Quinisext Council respectively. The development of rahbānīyyah informs our knowledge of the early Muslim community’s evolution into an imperial power around the time of the Caliph ‘Abd al-Mālik b. Marwān (d. 86/705).